Effects of epicardial adipose tissue volume and thickness assessed by computed tomography and echocardiography on cardiovascular and cerebrovascular outcomes: a systematic review and meta-analysis. (25th January 2023) - Chong, B; Jayabaskaran, J; Ruban, J; Goh, R; Chin, Y H; Kong, G; Ng, C H; Foo, R; Chai, P; Kong, W; Poh, K K; Chan, M Y; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Epicardial adipose tissue (EAT) has garnered attention as a potential imaging biomarker for the risk stratification of cardiovascular diseases (CVD). However, the prognostic utility of EAT due to inter-ethnic differences and imaging modality (computed tomography (CT) or transthoracic echocardiography (TTE)) remains undetermined. Purpose: To evaluate the effect of EAT volume and thickness on cardiovascular and cerebrovascular outcomes. We also aim to compare the prognostic utility between CT volumetric and TTE thickness quantification; and provide consolidated data on the heterogeneity in EAT measurements across different ethnic groups. Methods: Medline and Embase databases were searched from inception till 16 May 2022 for studies that measured EAT volume or thickness of adult patients at baseline and reported follow-up data on outcomes of interest. Outcomes included MACE, all-cause mortality, cardiac death, myocardial infarction (MI), coronary revascularisation, atrial fibrillation (AF), and stroke. Statistical analyses were conducted on Review Manager 5.4.1 to obtain unadjusted and adjusted hazard ratios (HR) and odds ratios (OR) with the results presented on forest plots. Results: Twenty-nine studies comprising 19709 patients were included in our analysis. Increased EAT thickness and volume were associated with higher risks of MACE (adjusted HR [aHR] 1.46, 95%CI 1.25–1.71, p<0.001), cardiac death (OR 2.53, 95%CI 1.17–5.44, p=0.020), MI (OR 2.63, 95%CI 1.39–4.96, p=0.003), coronary revascularisation (OR 2.99, 95%CI 1.64–5.44, p<0.001), AF (aOR 4.04, 95%CI 3.06–5.32, p<0.001), and stroke (HR 1.02, 95%CI 1.01–1.03, p<0.001). CT-volumetric quantification of EAT conferred a larger MACE risk (aHR 1.79, 95%CI 1.47–2.17, p<0.001) compared to TTE thickness quantification (aHR 1.20, 95%CI 1.09–1.32, p<0.001). Studies originating from North America (HR 1.91, 95%CI 1.26–2.89, p=0.002) and Asia (HR 1.60, 95%CI 1.09–2.36, p=0.020) demonstrated a significantly higher risk of MACE with increased EAT thickness and volume. However, this significance was not seen in European studies (HR 1.48, 95%CI 0.99–2.20, p=0.060). Subgroup differences were also noted across the studies' countries of origin when analysing the association of EAT and MI (p=0.020). European studies reported a higher magnitude of MI risk associated with higher EAT thickness and volume (OR 5.28, 95%CI 2.34–11.95, p<0.001) as compared to Asian studies (OR 1.75, 95%CI 1.05–2.92, p=0.030). No differences were noted across other outcomes in the subgroup comparisons by geographical region and between CT and TTE quantification of EAT. Conclusion: The utility of EAT as an imaging biomarker for predicting and prognosticating CVD is promising. Future efforts to harmonise the EAT parameter thresholds, based on the type of imaging modality and the target population's ethnic characteristics, will be the next important step before including EAT in CVD prediction models.